Growth and nutritional value of a Tropical Green Alga, Ankistrodesmus convolutus corda, in Agro-industrialeffluents - Habib, M. A. B.; Md Yusoff, Fatimah; Prang, S. M.; Mohamed Din, Mohamed Shariff (Universiti Putra Malaysia Press, 2004)
Use of agro-industrial effluents for microalgal culture was investigated using a tropical freshwater green alga, Ankistrodesmus convolutus cultured in various dilutions of latex concentrate effluent (LCRE), standard Malaysian rubber effluent (SMRE) and digested palm oil mill effluent (POMED). Ankistrodesmus convolutus grown in 40%and 60%LCRE, 60%SMRE and 10% POMED showed significantly higher (P < 0.05) specific growth rate in terms of cell number and chlorophyll a than that grown in other effluent media and inorganic fertiliser (N:P:K = 1:1:0.5) as control. Total biomass of this microalgae grown in 60%LCRE, 60%SMRE and 10% POMED was significantly higher (P < 0.05) than that cultured in other effluent media and the control. Ankistrodesmus convolutus cultured in 40% and 60% LCRE, 60% SMRE and 10% POMED showed significantly (P < 0.05) higher amount of crude protein and lipid than that grown in other effluent media and the control. Significantly higher (P < 0.05) amount of most of the essential amino acids (EAAs) except a few were found in A. convolutus cultured in 60% LCRE and 60% SMRE than that grown in other effluent media and control. Ankistrodesmus convolutus cultured in 10% POMED resulted in significantly higher (P < 0.05) amount of all the EAAs except threonine and tyrosine that were grown in other POMED media and control. Ankistrodesmus convolutus grown in 40% and 60% LCRE, contained significantly higher (P < 0.05) amounts of all the C18 and C20 polyunsaturated fatty acids (PDFAs) than that cultured in other SMRE media and control, except eicosadienoic acid (20: 2n-11). A similar trend of PUFAs was recorded in A. convolutus cultured in 60% SMRE except eicosatrienoic acid (20:3n-6) and arachidonic acid (20:4n-6). It was found that A. convolutus contained significantly (P < 0.05) higher amount of PUFAs such as linoleic acid (l8:2n-6), linolenic acid (18:3n-3) and arachidonic acid (20:4n-6) when grown in 10% POMED than that cultured in other POMED media and control. This study showed that A. convolutus grown in 40-60% rubber and 10% POMED has higher nutritional value that that cultured in other effluent media and inogranic fertilizer.